Analisis kuersetin pada ekstrak benalu teh (Scurrula oortiana Dans.) secara kuantitatif - Silvyana, Annysa Ellycornia; Reubun, Yonathan Tri Atmodjo; Warti, Lia; Simangunsong, Lidia Octaviani (Journal of Pharmaceutical and Sciences, 2025)
Indonesia has a variety of plants that are useful as medicine. One is the Tea Mistletoe plant (Scurrula oortiana Dans.). This plant contains flavonoid compounds that are effective as antioxidants, especially in the form of quercetin. Quercetin in the tea mistletoe plant can prevent cell damage caused by free radicals, where cells need this antioxidant to avoid the harmful effects of excessive reactive oxygen species (ROS) production and prevent damage to immune cells. This study aims to analyze the levels of quercetin in Tea Mistletoe extract using quantitative analysis methods such as thin-layer chromatography and UV-Vis spectrophotometry. Tea Mistletoe powder was extracted by maceration with 96% ethanol solvent and then concentrated using a rotary evaporator and water bath. The thick extract obtained was then tested for phytochemical screening and specific and non-specific parameters. Analysis of flavonoid quercetin compounds was carried out using a thin layer chromatography method using a mobile phase of a mixture of chloroform, ethyl acetate, and n-butanol with a ratio of 5:4:1 and a stationary phase of Silica Gel GF₂₅₄. Determination of flavonoid levels was carried out using UV-Vis spectrophotometry at a wavelength of 428 nm. The results of this study indicate that the Mistletoe Tea plant contains flavonoids, alkaloids, steroids, tannins, saponins, phenolics, and glycosides. All test parameters meet the specified requirements. The thin layer chromatography test showed the Rf value of the Mistletoe Tea extract of 0.78. The linearity test showed a correlation value (r) = 0.9988 with a total flavonoid compound content of 372.250 mg QE/g extract, or a percentage of 37.225%.